Healthcare Costs and Resource Use Associated With Cervical Intraepithelial Neoplasia and Cervical Conization: A Retrospective Study of German Statutory Health Insurance Claims Data - Anna-Janina Stephan; Miriam Reuschenbach; Kunal Saxena; Vimalanand S. Prabhu; Christian Jacob; Kim M. Schneider; Wolfgang Greiner; Regine Wölle; Monika Hampl (Journal of Health Economics and Outcomes Research)
**Background:** Cervical intraepithelial neoplasia (CIN) can be a consequence of human papillomavirus (HPV) infection. High-grade CIN (CIN2/CIN3) may develop from persistent HPV infection and progress to cervical cancer if left untreated. Management of CIN includes conservative surveillance or ablation and excision by conization. Internationally, CIN and its treatment generate a considerable economic burden, but no current data regarding costs and resource use from the perspective of the German statutory health insurance exist.